Association of carotid atherosclerotic plaque and intima-media thickness with the monocyte to high-density lipoprotein cholesterol ratio among low-income residents of rural China: a population-based cross-sectional study - Zhen Zhang; Yannan Gao; Zejian Li; Bingyi Li; Shuai Gao; Jiayi Sun; Jun Tu; Xianjia Ning; Wenjuan Zhang; Jinghua Wang (BMC, 2023)
Abstract Background The monocytes to high-density lipoprotein cholesterol ratio (MHR) has been identified as a potential biomarker for cardiovascular and cerebrovascular diseases. In this population-based cross-sectional study, we explored the relationships among carotid artery disease (CAD), including the presence of carotid atherosclerotic plaque (CAP) and carotid artery intima-media thickness (CIMT), the MHR, and related parameter changes. Methods This cross-sectional study, Conducted from April to June 2019 in a rural area of Tianjin, involved middle-aged and elderly participants. Based on carotid ultrasound examinations, participants were divided into CAP and non-CAP groups. Logistic regression and Receiver Operating Characteristic (ROC) curve analyses were utilized to assess MHR's predictive value for CAP. Gender-specific analyses were also performed to examine predictive variations. The relationship between CIMT and MHR was evaluated using linear regression. Results Of the 2109 participants meeting the inclusion criteria, 51.6% were identified with CAP. Multivariate analysis revealed a significant association between MHR and CAP prevalence, (OR, 9.670; 95% CI, 2.359-39.631; P = 0.002), particularly in females (OR, 5.921; 95% CI, 1.823-19.231; P = 0.003), after adjusting for covariates. However, no significant correlation was found between CIMT and MHR when adjusted for other factors. The ROC analysis showed the area under the curve for MHR and CAP to be 0.569 (95% CI: 0.544-0.593; P < 0.001). Conclusions These findings suggested that it is crucial to enhance early screening and intervention for CAD, specifically focusing on the prevention and progression of CAP, to address the unique health challenges faced by low-income groups in rural settings. Emphasizing these preventive measures could significantly contribute to improving cardiovascular health outcomes in this vulnerable population.